Prospects for applying a theory of change model to the use of research evidence in autism education - Mintz, Joseph; Roberts, Amelia (Frontiers in Education, 2023)
There has been continued interest in how schools can best make use of research evidence in bringing about change in practice in schools. A number of models have been developed to support schools in this challenge, such as research learning communities and lesson study. However, questions remain about the effectiveness of such models, their fit to the particular needs of schools and the extent to which they contribute meaningfully to the body of evidence used to inform changes to practice within the field of education. This issue is of particular relevance when considering the inclusion of children with autism in the classroom partly because of the large body of research being undertaken on autism across a range of domains with varying epistemological perspectives (e.g., neuroscience, psychology, pedagogy) and partly due to the widespread need to support children with autism in the classroom. Questions have also been raised about the evidence policy “agenda”, particularly in terms of reliance on positivist models centered on randomized controlled trials. These concerns focus on the extent to which performative or neoliberal perspectives on effectiveness might mask the complexity of how practice and knowledge (or evidence) are related in models of teacher professional working. One particular approach that could have potential in addressing these is that of Theory of Change (ToC). ToC models come from the field of theory-driven evaluation and draw on frameworks for relating practice to knowledge such as realist evaluation. ToC models consider under what conditions, for whom, and for what reasons or aims a given activity will achieve its intended outcomes. This paper considers the scope for the application of ToC models by reviewing a selected case from a completed study on the implementation of models for developing evidence informed practice in schools for autism education. By applying a ToC lens to what did happen in this case, we will “re-imagine” this case from a ToC perspective. This approach will serve to illustrate the possibilities for how ToC models could be used in future practice to advance evidence informed practice in autism education.